Economics and finance of lifelong learning - (:unkn) unknown (OECD, 2001)
"Learning is an essential basis for progress in the 'knowledge society'; it is critical for economic growth and social welfare. OECD Member countries have committed themselves to making lifelong learning a reality for all. But the resources required to meet that goal are potentially large and countries differ in their capacity to generate them. Can OECD Member countries rise to this challenge? This report seeks to provide some answers by identifying and examining the economic and financial issues that arise in implementing the goal, and the strategies that the public and private sectors are pursuing to achieve it. It deals with issues such as individual learning accounts, recognition of non-formal learning, and measures to raise rates of return to lifelong learning. The report is intended to provide a basis for continued in-depth discussion by public authorities and the social partners. It aims to inspire future actions that ensure that lifelong learning serves as a sustainable and equitable strategy for human development. The report draws on analyses, findings, and lessons from the OECD's earlier work and the proceedings of the international conference on ‚Lifelong Learning as an Affordable Investment'." (Editor, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; L 2.1.1 Informelles Lernen; S 2.3 Berufsbildungspolitik; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; OECD-Staaten; Bildungspolitik; Lebenslanges Lernen; Informelles Lernen; Bildungsfinanzierung; Kosten-Nutzen-Relation